HUBUNGAN DUKUNGAN SUAMI DAN TENAGA KESEHATAN PADA WANITA PASANGAN USIA SUBUR TERHADAP PEMILIHAN ALAT KONTRASEPSI IUD DI KEL. PANGKALAN MANSYUR KEC. MEDAN JOHORTAHUN 2020 - Hasibuan, Yusrawati; Padang, Arnianta Rizka; Hutabarat, Julietta (Colostrum Jurnal Kebidanan, 2021)
The high birth rate can cause population problems. To keep the birth rate can be prevented by using contraception. One contraceptive device that is still low in use is the Intra Uterine Device (IUD). The low use of an IUD can be caused by lack of husband support and counseling from health workers. This study aims to determine the relationship of husband and health workers’ support in women of fertile age with the selection of IUD contraception in Medan Johor community  health center of Pangkalan Mansyur village in 2020. This type of research was analytic survey with cross sectional design. The sample used was 60 fertile age couple who was IUD users and non-IUD users, as well as health workers totaling of 17 respondents. Data collection using a questionnaire and data analyzed with chi square test. The results showed that the majority of husbands did not provide emotional support (58.3%). The majority of husbands do not provide instrumental support (76.7%). The majority of husbands did not provide information support (86.7%). The majority of husbands did not provide award support (71.7%). The majority of health workers did not support (58.8%). The majority of fertile age couple did not choose an IUD (70%). There was a relationship between husband support for fertile age women and the selection of IUD contraception (p = 0,000). There was a correlation between the support of health workers in fertile age women and the selection of IUD contraception (p = 0.035). It is recommended that midwives routinely conduct counseling on IUD to individual or fertile age women group ; It is recommended that husbands should work to increase their support regarding the selection of an IUD. Keywords: Fertile Age Couple , IUD, Husband Support, Support of Health Workers